The impact of disclosure of environmental accounting on the quality of the performance of commercial establishments - Siralkhatim, Abeer Bakri (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aims to identify the reality of using environmental accounting in commercial establishments, as well as the amount of commercial enterprises ’interest in environmental accounting, in addition to identifying the difficulties and obstacles that commercial establishments face when applying environmental accounting. In order to achieve the objectives of the research, the descriptive and analytical approach was followed by describing the nature of environmental accounting, and electronic questionnaire was prepared and distributed to the study community represented by a group of accountants to survey their opinions. The research reached a set of results, the most important of which are: Commercial establishments disclose the procedures, programs and policies they adopt to preserve the environment, Environmental accounting is one of the most important types of accounting that is concerned with providing a clean environment free from environmental pollution, There are legislations and laws that bind commercial establishments to the rules and standards of environmental accounting, Environmental accounting is used to direct the environmental costs in commercial establishments, Environmental accounting helps to promote the culture and the concept of environmental safety in society, Disclosure of environmental information represents an urgent need for society in general and those dealing with commercial establishments in particular, The environmental accounting system is an important tool for disclosure of accounting information in commercial establishments. The research reached a set of recommendations, the most important of which are: Work on applying environmental accounting in commercial establishments because of its great benefit for society as a whole, Adopting specialized accounting courses to clarify the importance of disclosure of environmental accounting and the benefits that accrue to commercial establishments and society through its application, Establishing laws that regulate and oblige commercial establishments to set clear standards for environmental accounting.